1992
DOI: 10.1046/j.1468-2982.1992.1201021.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Salivary Magnesium Levels in Migraine and Tension-Type Headache. Results in a Group of Adult Patients

Abstract: It has been suggested that magnesium plays a central role in different etiopathogenetic conditions involved in the onset of migraine. We measured, by atomic absorption spectrophotometry, serum and salivary magnesium levels in drug-free migraine patients with and without aura and in tension-type headache patients. Migraine sufferers with and without aura and tension-type headache had significantly lower levels of serum and salivary magnesium concentrations in the interical periods than a group of healthy young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 17 publications
3
61
0
Order By: Relevance
“…This mutation may increase the levels of glutamate, leading to cortical hyperexcitability. On the other hand, there is ample evidence, both from basic and clinical studies, that decreased concentrations of ionized magnesium (Mg 2+ ) are associated with a decreased threshold for triggering a migraine attack (Mody et al 1987;Ramadan et al 1989;Sarchielli et al 1992). Decreased Mg 2+ concentrations also can activate NMDA receptors and, thus, can increase neuronal excitability.…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…This mutation may increase the levels of glutamate, leading to cortical hyperexcitability. On the other hand, there is ample evidence, both from basic and clinical studies, that decreased concentrations of ionized magnesium (Mg 2+ ) are associated with a decreased threshold for triggering a migraine attack (Mody et al 1987;Ramadan et al 1989;Sarchielli et al 1992). Decreased Mg 2+ concentrations also can activate NMDA receptors and, thus, can increase neuronal excitability.…”
Section: Glutamate Receptorsmentioning
confidence: 99%
“…As far as mood disturbances are concerned, it should be pointed out that neuromuscular hyperexcitability, demonstrated by the positive results of EMG ischemic tests, was associated in previous research with high levels of anxiety and/or stress [5,28]. Therefore we investigated in our patient groups the occurrence of anxiety and depression.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has established the role of magnesium deficiency in migraine, in adults [1][2][3][4][5][6][7], children and adolescents [8,9]. On the other hand, there is recurring evidence, since the early 1960s, that a relative or absolute lack of Mg ++ is related to certain neurological conditions such as criptotetany, latent tetany, hyperventilation syndrome and spasmophilia [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Others propose that stress triggers excretion of magnesium, with secondary hypomagnesemia causing a migraine (Durlach, 1976). During attacks as well as interictally, magnesium levels in both serum and saliva are decreased (Gallai et al, 1992), perhaps an indicator of low cerebral magnesium levels and therefore a decreased threshold for migraine development (Ramadan et al, 1989). Interictal studies on intracellular and serum levels in patients with migraines and tension--type headaches have shown inconsistent results.…”
Section: Migraine Pathogenesismentioning
confidence: 99%
“…Patients most susceptible to develop this condition include photophobic individuals that experience ophthalmological discomfort during visual stress tests. Sarchielli et al, (1992) showed that sufferers of migraine with and without aura, and tension--type headaches, exhibit significantly lower levels of serum and salivary Mg concentrations. Hypomagnesaemia raises the sensitivity of cerebral arteries to CO 2 which in turn favours cerebral vasospasm and headache (Thomas et al, 1994).…”
Section: Magnesium Interaction With Stress Pathwaysmentioning
confidence: 99%